1998
DOI: 10.1016/s0014-5793(98)01275-7
|View full text |Cite
|
Sign up to set email alerts
|

Atractyloside‐induced release of cathepsin B, a protease with caspase‐processing activity

Abstract: Recent data show that a strong relation exists in certain cells between mitochondria and caspase activation in apoptosis. We further investigated this relation and tested whether treatment with the permeability transition (PT)-inducing agent atractyloside of Percoll-purified mitochondria released a caspase-processing activity. Following detection of procaspase-11 processing, we further purified this caspase-processing protease and identified it as cathepsin B. The purified cathepsin B, however, was found to be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
213
0
1

Year Published

2001
2001
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 290 publications
(224 citation statements)
references
References 38 publications
10
213
0
1
Order By: Relevance
“…Our experiments using specific protease inhibitors suggest the involvement of non-caspase proteases in CEACAM1-4L-induced apoptosis including aspartate proteases, metalloproteinases and cathepsin B. In fact, activation of caspase-1 by cathepsin B and inhibition of the corresponding apoptosis pathway by the addition of Z-VAD.fmk have been well documented (Vancompernolle et al, 1998). It is thus likely that procaspase activation may be initiated by these proteases.…”
Section: Activation and Processing Of Ceacam1 During Apoptosis S Nittmentioning
confidence: 60%
“…Our experiments using specific protease inhibitors suggest the involvement of non-caspase proteases in CEACAM1-4L-induced apoptosis including aspartate proteases, metalloproteinases and cathepsin B. In fact, activation of caspase-1 by cathepsin B and inhibition of the corresponding apoptosis pathway by the addition of Z-VAD.fmk have been well documented (Vancompernolle et al, 1998). It is thus likely that procaspase activation may be initiated by these proteases.…”
Section: Activation and Processing Of Ceacam1 During Apoptosis S Nittmentioning
confidence: 60%
“…In particular, some forms of apoptosis can be inhibited by blocking cathepsin B. It is of interest that many peptide caspase inhibitors are also capable of blocking cathepsin B activity both in vitro and in cells [36,37]. Furthermore, cathepsin B has been shown to process caspase 3 under neutral conditions, albeit weakly [37].…”
Section: Discussionmentioning
confidence: 99%
“…24 Alternatively, cathepsins could cleave and activate caspases or their downstream death effector substrates, 25 thereby causing apoptosis. In support of the former mechanism, it has been shown that cathepsin B can activate the inflammatory caspases 1 and 11, 17,26 and that cathepsin L may activate caspase-3. 20 The final possible mode of cathepsin action places cathepsins far upstream in the apoptotic cascade, cleaving the proapoptotic Bcl-2 family member Bid to initiate mitochondrial release of cytochrome c. This last hypothesis received in vitro confirmation when it was shown that lysosomal extracts containing cathepsins were able to cleave purified Bid in a physiologically relevant manner that supported apoptosis.…”
Section: Introductionmentioning
confidence: 90%
“…[3][4][5][6][7][8][9][10][11][12][13][14] Although cathepsins normally reside in the lysosome and carry out nonselective degradation of proteins, a strong case was made for the involvement of these proteases in apoptosis when it was shown that agents that disrupted lysosomes and caused cathepsins to redistribute to the cytoplasm inevitably resulted in apoptosis. 13,[15][16][17][18][19] Similarly, cathepsin inhibitor treatment blocked this apoptosis. 11,14,[18][19][20][21][22] Theoretically, the cathepsin proteases could induce apoptosis by a variety of different mechanisms.…”
Section: Introductionmentioning
confidence: 94%